Penyusunan Konsep Naratif Tiga Babak Dalam Penyutradaraan Film Dokumenter “Ngindung ka Waktu Mibapa ka Jaman” - Novita, Dwi Putri; Nugroho, David Rizar (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2025)
The documentary film “Ngindung ka Waktu Mibapa ka Jaman” was inspired by concerns about the declining interest of the public, especially the younger generation, in gamelan as one of Indonesia’s cultural heritages. The rapid development of technology and popular culture has marginalized gamelan from everyday life. This study aims to apply the concept of three-act narrative directing in building a documentary film plot that is not only informative, but also emotional and easy for the audience to understand. The three-act narrative structure consists of introduction, confrontation, and resolution, which are used to structure the story journey. The type of documentary used is a participatory documentary, where the director is actively and interactively present in the interview process and narrative development. The resource person becomes the subject who forms the narrative based on their experiences, especially gamelan craftsmen and cultural figures in Bogor. The results of the application of this concept show that the three-act narrative structure is able to build a documentary plot that is both emotionally and communicatively strong. This film is expected to be an effective educational media to revive public awareness of the importance of preserving gamelan culture amidst of the modernization era.